Partidos políticos e eleições em Joaçaba : origem e composição social (1947-1960) - Gerardi, Dirceu André (2010)
This paper search into origin and the social composition of political parties in the city of Joaçaba. The historical clipping we have selected, will begin with the introduction of the Fourth Republic in 1945 until 1960. The object of study are political parties PSD, UDN and PTB and elections, noted in three subsystems, the national, state and local levels. Between the purposes it is to the inquiry of the historical origins of the parties, the social compositions and the electoral performance of the associations in the city of Joaçaba and region. We deal with the formation of national parties, in Santa Catarina, and their genesis in Joaçaba. The formation of parties in SC after 1945 is going to demonstrate the presence of oligarchies (Ramos and Konder-Bornhausen) that are create from old political structures before the New State, and which directly influenced the formation of the PSD in Joaçaba. For it understand the connections between the parties Joaçaba, state and the oligarchs who were the elements who are part of the political parties. We propose a study of the social composition of the (PSD, UDN and PTB) of Joaçaba. The genesis of the parties in the city, had it influences of the state oligarchies, in big measure in case of the PSD and some in the UDN. The PTB does not suffer apparent influence. PSD and UDN, arregimentaram its pictures politicians in the economic and industrial elite (local and regional). However PSD was a party of traders and industrialists and traders UDN settled equitably. The PTB in 1947 to bring its orbit, the workers (who worked in trades and industries of the leaders of the PSD and UDN), suffering later radical modifications in its composition. In such case, determine the origin of parties in Joaçaba implicate in the study of social compositions of associations, observed through the members of municipal directories, candidates (the Mayor and councilor), and elects. Determined that the political relations were in the same time economic and social. Socioeconomic profile was deciding factor in the choice of candidates by parties and determinant of its victories and defeats. PSD and UDN were parties highly elitizados. The PTB was merged, but the workers do not arrived to occupy important positions in the party